Edukasi Kewirausahaan Dasar Bagi Keluarga Penerima Program Keluarga Harapan (PKH) Kelurahan Dusun Besar Kecamatan Singgaran Pati Kota Bengkulu - Novrianda, Herry; Nengsih, Mimi Kurnia; Shar, Aan; Mikaresti, Pamella; Herlina, Meti (Jurnal Dehasen Untuk Negeri, 2025)
The Family Hope Programme (PKH) is an effort to accelerate poverty by the Government of Indonesia since 2007. The community receiving PKH assistance tends to be passive in managing the assistance received, so that the positive impact on improving the quality of life is still limited and seems to wait or depend on the next assistance (periodic assistance). Dusun Besar Village is one of the villages that is still a PKH beneficiary, namely 115 households. Based on the survey results, it can be concluded that partners (PKH group in Dusun Besar Village) need training and assistance to be able to achieve the long-term goals of the PKH programme. The training and assistance needed is a Marketing Management Workshop on basic entrepreneurship. The purpose of the Community Service aims to provide education and strengthening about basic entrepreneurship through workshops and training activities for PKH beneficiary families in Dusun Besar Village, Singaran Pati District, Bengkulu City. This activity is carried out with stages of problem identification, training consisting of lecture, discussion and hands-on practice methods as well as mentoring, monitoring and evaluation. Participants of this activity are members of PKH beneficiaries from Dusun Besar Village, totalling 35 people. The results showed an increase in knowledge, motivation and skills of partners which had an impact on improving the welfare of families receiving the PKH programme in Dusun Besar Village, Singaran Pati District, Bengkulu City.